An empirical analysis of the Determinants of Real GDP Growth in Sierra Leone from 1980-2018 - Mohamed Samba Barrie (ZBW – Leibniz Information Centre for Economics, 2020)
The purpose of the research was the exploration of macroeconomic determinants of economic growth in Sierra Leone for the period, 1980- 2018, and whether there exist an association between the determinants and economic growth is long-term and short-term. The research methodology was quantitative and it was limited to eight mostly macro-fiscal variables and the empirical model employed was the Autoregressive Distributed Lag model. The findings revealed foreign direct investment was positive in both the short and long run but only statistically significant at the 10% level in the short-run dynamic model. Gross capital formation and population growth were also positive and statistically significant in determining RGDP growth in both the static long-run and dynamic short-run models. Openness to trade has a negative and significant impact on RGDP growth in the short run but insignificant in the long run. On the other hand, real exchange fluctuations, domestic credit rate, private remittances are negative and statistically significant towards RGDP growth. The dummy variable war is significant in both long and short-run but exerted no negative impact on RGDP. The other dummy variable Ebola had the expected negative sign both in the long run and short-run but it is also statistically insignificant. Also, applying the Bounds test Cointegration model, the findings revealed a statistically significant long-run association between economic growth and the specified determinants (F-statistics value= 15.18749, and an upper bound value or I(1) value = 2.08). Furthermore, the error correction model applied to determine the short-run deviation from the long-run had the expected sign, and was statistically insignificant (ECM = -0.131559), indicating convergence towards equilibrium occurred at the rate of 13% in the period under review. However, the research was limited to predominantly macro-fiscal variables, future research must also look at the impact of monetary variables.
Keywords: 330; Growth determinants; Sierra Leone; ARDL approach; applied econometrics; macro-fiscal variables